Individual-typological and socio-psychological features of university students with different levels of readiness to participate in sports competitions - Pashchenko L.G. ,; Romanko O.A. ,; Kaiipbekova I.U. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to study the individual typological and socio-psychological characteristics of university students with different levels of subjective readiness to participate in sports competitions. Methods and structure of the study. 356 students (142 boys, 214 girls) of 1st–3rd year students of Nizhnevartovsk State University took part in the scientific work. All participants provided consent to conduct diagnostics and process personal data. Results and conclusions. An individual’s subjective readiness to participate in competitions is correlated with indicators of extraversion and introversion. Students with a dominant choleric type of temperament show greater readiness to participate in sports competitions, while those with a melancholic type show the least readiness. Among students with predominant sanguine and phlegmatic types of temperament, such tendencies were not identified. Constructive behavioral strategies for interpersonal interaction (cooperation and compromise) are noted among individuals with an average and above average level of readiness to engage in rivalry in competitive conditions. Students who are ready to take part in competitions demonstrate the best results in testing strength endurance, which requires the manifestation of volitional efforts. The results obtained indicate the need to search for and scientifically substantiate new competitive practices that satisfy the individual characteristics of university students, and their implementation in educational and extracurricular forms of physical education.